Effects of inorganic-organic fertilization schemes on the soil carbon fixation microbial communities and organic carbon accumulation - Kong, Chenchen; Ye, Huichun; Zhang, Shiwen; Wang, Shan (International Journal of Agricultural and Biological Engineering, 2025)
This study aimed to elucidate the effects of different fertilization on the accumulation of soil organic carbon (SOC) and the community structure of carbon fixation bacteria in farmland, as well as their carbon sink mechanisms. Four field-based treatments were set up: no fertilizer (CK), organic fertilizer (OF), inorganic fertilizer (CF), and organic-inorganic compound fertilizer (OCF). Differences in soil cbbL bacterial communities, SOC and its component contents, and carbon pool management indices were analyzed using methods such as NMDS, Anosim, and metagenomeSeq tests. The aim was to identify the key differential species under different fertilization treatments, analyze the response relationship between cbbL bacteria communities and SOC and its component content, and clarify the important carbon fixation functional genes. The main findings were as follows: 1) CF and OCF significantly reduced soil cbbL bacterial diversity (p<0.05). Significant differences were observed among cbbL bacterial communities under different fertilization treatments (p=0.001). CK and OF treatments had higher numbers of unique OTUs and similar species composition. The six bacterial orders with significant differences among different fertilization treatments predominantly belonged to Pseudomonadota and Actinomycetota. 2) The CF treatment had the lowest content of SOC and its components, and carbon pool management indices. OF and OCF were beneficial to the improvement of SOC and its components, but there was no significant difference between the groups (p>0.05). Short-term fertilization differences had no significant effect on the carbon pool management index (p>0.05). 3) Compared with cbbL bacterial diversity, the differentially abundant species had a higher contribution to SOC accumulation (83.90%). Among them, Chromatiales significantly affected the active components of SOC and the carbon pool management index (p=0.04). Thiodictyon was a major functional genus under this order that had a significant positive effect on SOC (p=0.034), with the application of organic fertilizer exhibiting a targeted effect, promoting its abundance. The research results have revealed the key pathways for regulating microbial carbon fixation through fertilization, providing a novel theoretical basis and practical targets for carbon fixation and emission reduction in farmland ecosystems. Key words: fertilization type; soil organic carbon; cbbLbacterial community; response relationship; carbon fixation functional genes DOI: 10.25165/j.ijabe.20251806.9970 Citation: Kong C C, Ye H C, Zhang S W, Wang S. Effects of inorganic-organic fertilization schemes on the soil carbon fixation microbial communities and organic carbon accumulation. Int J Agric & Biol Eng, 2025; 18(6): 158–167.